Answer:
m=(-6,6)
Step-by-step explanation:
m^2 -36 = 0
Reorder the terms:
-36 + m^2 = 0
Solving for variable 'm'.
Add '36' to each side of the equation.
-36 + 36 + m^2 = 0 + 36
Combine like terms: -36 + 36 = 0
0 + m^2 = 0 + 36
m^2 = 0 + 36
Combine like terms: 0 + 36 = 36
m^2 = 36
Simplifying
m^2 = 36
Take the square root of each side:
√m^2=+/-√36
m=(+/-)6
m = {-6, 6}
Answer:
JK got 30 answers correct on a 50 item test.
Step-by-step explanation:
It is given that:
Total items on test = T = 50
Fraction of total items that were answered correctly = 3/5
We simply have to multiply the total number of questions by the fraction of correct answers.
So,
The correct answered number of items are:
![= \frac{3}{5} * 50\\=30](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B3%7D%7B5%7D%20%2A%2050%5C%5C%3D30)
Hence,
JK got 30 answers correct on a 50 item test.
ABC and CBH are right angles
DBC = 90 - 37 = 53
CBJ = 90 - 31 = 59
HBD = 180 - 37 = 143
or
HBD = 31 + 53 + 59 = 143 :)
What says odd integers???
Answer:
b hopefully this helps you with work